The critical role of Sirt1 in ischemic stroke - Jia, Ziyi; Xu, Ke; Li, Ruobing; Yang, Siyu; Chen, Long; Zhang, Qianwen; Li, Shulin; Sun, Xiaowei (Frontiers in Pharmacology, 2025)
Ischemic stroke, the most prevalent form of stroke, is responsible for the highest disability rates globally and ranks as the primary cause of mortality worldwide. Sirt1, extensively investigated in neurodegenerative disorders, is the most well-known and earliest member of the sirtuins family. However, its mechanism of action during ischemic stroke remains ambiguous. The literature examination revealed the intricate involvement of Sirt1 in regulating both physiological and pathological mechanisms during ischemic stroke. Sirt1 demonstrates deacetylation effects on PGC-1α, HMGB1, FOXOs, and p53. It hinders the activation of NLRP3 inflammasome and NF-κB while also engaging with AMPK. It regulates inflammatory response, oxidative stress, mitochondrial dysfunction, autophagy, pro-death, and necrotic apoptosis. Therefore, the potential of Sirt1 as a therapeutic target for the management of ischemic stroke is promising.